Modeled Structure of the Cell Envelope Proteinase of Lactococcus lactis - Hansen, Egon Bech; Marcatili, Paolo (Frontiers in Bioengineering and Biotechnology, 2020)
The cell envelope proteinase (CEP) of Lactococcus lactis is a large extracellular protease covalently linked to the peptidoglycan of the cell wall. Strains of L. lactis strains are typically auxotrophic for several amino acids and in order to grow to high cell densities in milk they need an extracellular protease. The structure of the entire CEP enzyme is difficult to determine experimentally due to the large size and due to the attachment to the cell surface. We here describe the use of a combination of structure prediction tools to create a structural model for the entire CEP enzyme of Lactococcus lactis. The model has implications for how the bacterium interacts with casein micelles during growth in milk, and it has implications regarding the energetics of the proteolytic system. Our model for the CEP indicate that the catalytic triad is activated through a structural change caused by interaction with the substrate. The CEP of L. lactis might become a useful model for the mode of action for enzymes belonging to the large class of S8 proteinases with a PA (protease associated) domain and a downstream fibronectin like domain.